IbM Peningkatan Psychological Wellbeing pada Guru SMK Muhammadiyah 1 Purwokerto - Wibowo, Ugung Dwi Ario; Suwarti, S (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
Society service aims: to help teachers able to interpret the work and life according to the desired psychological conditions, thus requiring increased self-skill to build psychological wellbeing. Society service is used by a number of 28 teachers SMK Muhammadiyah 1 Purwokerto. Training sessions of Psychological Wellbeing on the Teacher are: (1) Know the concept of